Risk Sensitivity of Banks, Interbank Markets and the Effects of Liquidity Regulation - Thilo Pausch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The industrial organization approach to banking is extended to analyze the effects of interbank market activity and regulatory liquidity requirements on bank behavior. A multi-stage decision situation allows for considering the interaction between credit risk and liquidity risk of banks. This interaction is found to make a risk neutral bank behave as if it were risk averse in an environment where there is no interbank market and liquidity regulation. Introducing a buoyant interbank money market destroys endogenous risk aversion and allows banks to manage credit risk and liquidity risk independently. The paper shows that a liquidity regulation just like the one proposed in BCBS (2010) is not generally able to offset the separating effect of interbank money markets and recreate endogenous risk aversion of banks.
Keywords: G21; G28; G32; 330